Industrial confidence predicting stock market returns: Nordic evidence - Korhonen, Joonas (My University, 2016)
The outcome of monthly confidence surveys is an important piece of economic information and provides a stable indicator for business sentiment. The purpose of this thesis is to examine the relationship between industrial confidence indicators and the stock markets of Nordic countries. Especially, whether the industrial confidence indicators provided by European Commission predict stock market returns in Finland, Sweden, Norway or Denmark. The countries that are dependent on trading with European’s greater markets. The simple OLS –regressions reveal that the industrial confidence of euro area has some predictive power over stock market returns in Nordic countries. This relationship is further analyzed with vector autoregressive methods. The VAR and VECM models disprove the findings. However, the dummy variable of positive change is proven to be statistically significant at 1% level in all studied regions while the dummy variable of negative change is zero. Thus, the magnitude of change seems to be rather irrelevant. The results of positive dummy variables are used with the industrial confidence based investment strategy. In the empirical part of this study, back testing shows that investors would have been able to generate up to three times the market profits with less risk by timing their investment according the changes in industrial confidence. This would have meant 3283% returns in 27 years in Norway versus the index return of 990%.
Keywords: industrial confidence; market anomaly; efficient market theory; fi=Laskentatoimi ja rahoitus|en=Accounting and Finance|; fi=Master's Degree Programme in Finance|